2022
DOI: 10.1053/j.semnuclmed.2021.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Safe Pulmonary Scintigraphy in the Era of COVID-19

Abstract: One of the major effects of the COVID-19 pandemic within nuclear medicine was to halt performance of lung ventilation studies, due to concern regarding spread of contaminated secretions into the ambient air. A number of variant protocols for performing lung scintigraphy emerged in the medical literature which minimized or eliminated ventilation scintigraphy, due to the persistent need to provide this critical diagnostic service without compromising the safety of staff and patients. We have summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…While there are some attempts to clarify the role of Q-only or hybrid imaging (with SPECT/CT or low-dose CT), it remains elusive as to whether Q-only imaging is a reliable method of assessing PE during and after the pandemic. [ 15 16 ] The present study incorporates a meticulous pretest probability analysis of the patients to improve the insufficient specificity of the Q-only scintigraphy, which is of greater importance, especially in the oncologic patient populations. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are some attempts to clarify the role of Q-only or hybrid imaging (with SPECT/CT or low-dose CT), it remains elusive as to whether Q-only imaging is a reliable method of assessing PE during and after the pandemic. [ 15 16 ] The present study incorporates a meticulous pretest probability analysis of the patients to improve the insufficient specificity of the Q-only scintigraphy, which is of greater importance, especially in the oncologic patient populations. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 16 ] The present study incorporates a meticulous pretest probability analysis of the patients to improve the insufficient specificity of the Q-only scintigraphy, which is of greater importance, especially in the oncologic patient populations. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…For example, several proposals to modify established guidelines during the pandemic were considered by the Society of Nuclear Medicine and Molecular Imaging (SNMMI) and by the European Association of Nuclear Medicine (EANM) including the routine use of ventilation (V) scanning for the evaluation of PE. 26 , 27 , 28 Because lung scintigraphy often induces coughing and can contaminate air with minute amounts of radioactivity and aerosolized COVID-19, the ‘V’ component of V/Q SPECT raised concern as a source of potential spread of viral contagion. 29 As a result, the nuclear medicine community implemented and evaluated novel approaches to lung scintigraphy to adapt to the COVID-19 pandemic in an attempt to mitigate contagion risk to both patients and staff.…”
Section: Spect/ct For Pulmonary Embolism and Cardiac Imaging In Covid-19mentioning
confidence: 99%
“…The authors found that ∼80% of these patients demonstrated less than one segmental perfusional defects and were cleared of PE without the need for further imaging whereas patients with >1 perfusion defects were subsequently referred for additional testing such as pulmonary CTA where appropriate. 26 …”
Section: Spect/ct For Pulmonary Embolism and Cardiac Imaging In Covid-19mentioning
confidence: 99%
“…We analyzed a sample of pregnant women who underwent pulmonary perfusion scintigraphy to rule out the suspicion of PTE during admission to our center (Hospital Universitario Juan Ramón Jiménez, Huelva, Spain) for acute COVID-19 infection. It is important to note that at the beginning of the pandemic we adapted our pulmonary SPECT protocol according to the recommendation 13 , 14 of removing the ventilation component due to the risk of contagion and contamination by SARS-CoV-2, and therefore, we performed perfusion scintigraphy in a SPECT/CT modality. In the case of pregnant women, the CT component was also withdrawn.…”
Section: Introductionmentioning
confidence: 99%